ANALISIS PENGARUH CELEBRITY ENDORSER/BRAND AMBASADOR, HARGA DAN DESAIN PRODUK YANG DIMEDIASI OLEH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI ONLINE SHOP SHOPEE - Reni Febriani; Mirza Abdi Khairusy (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
This research aimed to analyze the effects of celebrity endorser/brand ambasador, price, design product on brand image to purchase decision on Shopee at online shop Desstore Collection Serang. The research object which do in this case is the Desstore Collection consumer who has made a purchase. There are 100 respondents and this research used probability sampling by using simple random sampling technic. The data analyze technic which used in this case is the structural equation model (SEM) by Partial Least Square (smart PLS 3.0). The data is primary and uses a questionnaire online with open and closed questions. The result of this research 5 hypothesis accepted and 2 hypothesis rejected. The 5 hypothesis accepted are price and brand image positively affected to purchase intention, brand ambasador, price and design product positively affected to brand image. 2 hypothesis rejected is show celebrity endorser negatively affected to purchase intention and design product not significant but positively affected to purchaseintention.